Meningkatkan Keterampilan Membuat Vas Bunga Koran Melalui Metode Demonstrasi pada Anak Tunagrahita Ringan - Soniatri, Novyolla; Ardisal, Ardisal (Inovan Publisher, 2024)
This research is motivated by the problems found in class VII SLB Amal Bhakti Warga Selayo Kab Solok, in one practice room there are two mentally retarded students who are not yet skilled in making skills from used goods. Previously, the children had learned skills from used goods such as tissue boxes, dowry boxes, and flowers but were not successful in the process, therefore this research was conducted using used newspaper items through the demonstration method. This research will be carried out in two cycles, each cycle consisting of from: planning, implementing actions, observation and reflection. The data collection techniques used were observation, documentation, and action tests. Based on the results obtained by students using two cycles, namely the EA value in the action cycle I was 73%, and in cycle II obtained a value of 95%, while SI students obtained a value in cycle I which was 59%, and in cycle II obtained a value of 91 %. Based on the data above, the conclusion of the skill of making flower vases from used newpaper has increased significantly through the demonstration method.